Peran E-Marketing Dalam Optimalisasi Destinasi Wisata: Analisis Konten dan Pendekatan Konseptual - Irma Kharisma Hatibie; Srilian Laxmiwaty Dai (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2020)
Electronic marketing used in the industry has made this advice and infrastructure one of the media and goals in realizing tourist destinations. In the service industry, the use of electronic marketing can personalize targeted customers' personal information. This personalization includes a stage where consumers or potential customers increasingly expect unbeatable service to their desires. This means that the use of electronic marketing has benefits in attracting potential tourists, there are challenges on how to adjust information or forms of marketing on social media related to tourist desires, or how to attract the attention of potential tourists to decide to travel. The purpose of this research is to answer the challenges of using electronic marketing to achieve marketing optimization. Analysis of the content from the use of social media and what conceptual approaches can optimize the role of electronic marketing. This research method uses analytical content related to electronic marketing, namely social media which is often used in Indonesia. This paper presents an interpretation of the results of the analysis between the market needs of tourists and combines the purpose of users using their application to obtain information so that it can lead them to travel decisions.